2013
DOI: 10.4236/ojpsych.2013.31003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychiatric morbidity among inmates in Jos maximum security prison

Abstract: Background: The prevalence of psychiatric illness in correctional settings is significantly elevated, with higher than community rates reported in most mental disorders. The prison is a correctional institution in which inmates have limited liberty, autonomy, and communication with family and friends. This can be devastating to some inmates thereby leading to deterioration in their physical, psychological and social wellbeing. The study was aimed to determine the prevalence of axis 1 psychiatric disorders and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 19 publications
12
28
1
Order By: Relevance
“…This finding was strengthened by the result from Jos maximum Security Prison, Plateau State which indicated a strong association between depression and status of prison [27]. The possible explanation for this could be age distributions of the prisoners as the distribution of old ages were higher in the Gondar and Dabre Tabor prisons.…”
Section: Discussionmentioning
confidence: 94%
“…This finding was strengthened by the result from Jos maximum Security Prison, Plateau State which indicated a strong association between depression and status of prison [27]. The possible explanation for this could be age distributions of the prisoners as the distribution of old ages were higher in the Gondar and Dabre Tabor prisons.…”
Section: Discussionmentioning
confidence: 94%
“…[16] and Armiya'u et.al. [17] who reported a SUD prevalence of 26.1%, 20.1% and 48.7% in their respective samples [15][16][17]. A more recent study conducted at a maximum security prison in Nigeria among awaiting trial and convicted inmates showed that 60% of the inmates had used alcohol and illegal drugs before their current offense [14].…”
Section: Discussionmentioning
confidence: 99%
“…Other previous studies of psychiatric comorbidity in Nigeria have documented a relatively low prevalence of SUD in prison populations [15][16][17].…”
mentioning
confidence: 99%
“…Findings indicate limitations in provision of psychosocial health services for displaced people, including management of severe mental disorders and lack of referral mechanisms to specialized mental health services [1]. Psychiatric morbidity is generally defined as a psychological or mental condition which leads to both psychological and physical deterioration [2]. The term usually applies to people who are very aware of their condition, despite the psychological and physical deterioration [2].…”
Section: Introductionmentioning
confidence: 99%
“…Psychiatric morbidity is generally defined as a psychological or mental condition which leads to both psychological and physical deterioration [2]. The term usually applies to people who are very aware of their condition, despite the psychological and physical deterioration [2]. Psychological distress, posttraumatic stress disorder and major depressive episode have been recognized as the most common mental health issues amongst the uprooted populations [3,4].…”
Section: Introductionmentioning
confidence: 99%